Evolution of the construction of a pedagogical model for m-learning activities (Research, Society and Development, 2019)
The purpose of this article is to present the evolution of the construction of a pedagogical model for m-learning, called ML-SAI, which was based on the concept of Inverted Classroom. In this sense, it is initially defined what this study understands by pedagogical model, m-learning and Inverted Classroom. Following are the methodologies and procedures for the elaboration of the same. Next, the ML-SAI pedagogical model is described, describing its architecture and providing some suggestions of strategies for the orientation of teachers interested in using it in the development of m-learning activities. Finally, it is reported an experimentation of the proposed pedagogical model, accomplished through a practical activity in an Information Systems course. The ML-SAI proposal presented good results, allowing collaboration in the planning and consistent development of pedagogical practices and better utilization of technological resources, providing some suggestions of strategies to teachers and researchers interested in using it, guiding them in the development of activities of m -learning. Being well accepted in the test performed.